2014
DOI: 10.1128/aac.02910-14
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Safety Outcomes of Patients Receiving Daptomycin with HMG-CoA Reductase Inhibitors

Abstract: dDaptomycin, a cyclic lipopeptide antibiotic, and 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors (statins) are commonly administered in the inpatient setting and are associated with creatine phosphokinase (CPK) elevations, myalgias, and muscle weakness. Safety data for coadministration of daptomycin with statins are limited. To determine the safety of coadministration of daptomycin with statin therapy, a multicenter, retrospective, observational study was performed at 13 institutions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 19 publications
1
58
2
1
Order By: Relevance
“…However, it is not suitable to exceed the dose of 6 mg/kg in patients with obesity and creatinine clearance less than 50 ml/min (Gutiérrez Urbón et al 2013). Daptomycin and statins when administered together caused creatine phosphokinase elevations, muscle pain and muscle weakness (Bland et al 2014). Even when exposed to daptomycin of 100-fold MIC concentration, some Staphylococcus aureus SA113 survived.…”
Section: Issues To Overcome and Solutionsmentioning
confidence: 98%
“…However, it is not suitable to exceed the dose of 6 mg/kg in patients with obesity and creatinine clearance less than 50 ml/min (Gutiérrez Urbón et al 2013). Daptomycin and statins when administered together caused creatine phosphokinase elevations, muscle pain and muscle weakness (Bland et al 2014). Even when exposed to daptomycin of 100-fold MIC concentration, some Staphylococcus aureus SA113 survived.…”
Section: Issues To Overcome and Solutionsmentioning
confidence: 98%
“…Bland et al's study compared 220 patients receiving daptomycin (49 with statins vs 171 without statins) and did not find statistically significant differences in frequencies of myalgia (6.1% vs 2.9%, respectively; p = 0.38), CK levels of >1,000 U/ liter (10.2% vs 5.3%, respectively; p = 0.32), or therapy discontinuation due to CK elevations with concurrent myalgia (6.1% vs 3.5%, respectively; p = 0.42). [21]. Berg et al's study compared 498 patients receiving daptomycin (63 with statins and 384 without statins) and did not find a statistically significant difference in frequency of CK elevation (Hazard Ratio, 0.44; 95% Confidence Interval, 0.14-1.40; p = 0.17) [22].…”
Section: Statins Interactions With Daptomycinmentioning
confidence: 99%
“…The prescribing information for daptomycin recommends considering suspending statin during treatment with daptomycin [49]. To date, studies have not found a higher risk of adverse outcomes with concomitant administration; however, these studies are retrospective and could be underpowered [21][22][23][24][25].…”
Section: Statins Interactions With Daptomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant use of other agents that may cause myopathy, including inhibitors of 3-hydroxy-3-methyl-glutarylcoenzyme A reductase (statins), may increase the risk of increasing the levels of creatinine phosphokinase and should be avoided if possible. 15 Data are limited on the coadministration of daptomycin and statins, and results of a recent retrospective observational study 24 indicated a slightly higher incidence of elevations in creatinine phosphokinase level when combination therapy was used (6.1% vs 2.9%; P = .38). Elevations in phosphokinase level rarely result in discontinuation of therapy.…”
Section: Alternative Treatments For Mrsa Infectionsmentioning
confidence: 99%